The Decline of the Middle Class: New Evidence for Europe. Issue 4 (2nd October 2021) - Derndorfer, Judith; Kranzinger, Stefan
Abstract: This article examines how the middle class has fared in twenty-six European countries between 2004 and 2014 based on European Survey on Income and Living Conditions (EU-SILC) data. We define individuals living in households with a median equivalized disposable household income between 75% and 125% to be middle class. We find that the middle class has decreased in eighteen out of twenty-six countries, which is accompanied by an increase of income polarization. Income redistribution is most influential for explaining differences in the size of the middle class across European countries. Supplemental data for this article is available online at https://doi.org/10.1080/00213624.2021.1982338